Race and the Subject of Masculinities - Uebel, Michael; Stecopoulos, Harry (Book collections on Project MUSE., 1997)
Although in recent years scholars have explored the cultural construction of masculinity, they have largely ignored the ways in which masculinity intersects with other categories of identity, particularly those of race and ethnicity. The essays in Race and the Subject of Masculinities address this concern and focus on the social construction of masculinity - black, white, ethnic, gay, and straight - in terms of the often complex and dynamic relationships among these inseparable categories.